Comparative Performance of Rectangular, Low and High Aspect Ratio Cambered Otterboards - M., Mukundan; M., Shahul Hameed (Fishery Technology, 2025)
The performance of two cambered otterboard types (low and high aspect ratio) when used with 17 m and 24 m demersal trawls were measured. The parameters included were loads on different points, total load, vertical opening, door and wing-end spreads and angle of attack, heel and tilt of door. The vertical opening of the trawls were 1.5-1.6m. The vertical curved board spread the net more. The sheer force calculated was between 70 to 140 kgf for the high aspect ratio board and was between 45 to 98 kgf for the other. Based on the study, the cambered board of high aspect ratio is recommended as an efficient substitute for rec- tangular Hat otterboard in common use